2020
DOI: 10.1590/s1413-41522020193204
|View full text |Cite
|
Sign up to set email alerts
|

Situação sanitária e o uso da água do Igarapé Santa Cruz, município de Breves, Arquipélago de Marajó, Pará, Brasil

Abstract: RESUMO O estudo teve por objetivo verificar e avaliar a situação sanitária e o uso e qualidade das águas do Igarapé Santa Cruz, no município de Breves, Pará. Para obtenção dos dados, aplicou-se um questionário que abordou o uso das águas e as condições sanitárias dos moradores às margens do igarapé. Também foi realizada a coleta de água para as análises bacteriológica e dos parâmetros físico-químicos, em quatro pontos do igarapé, nos quais foram feitas duas medições para cada parâmetro a ser analisado, sendo u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…The detection of fecal coliforms confirms that the water used by the population and for irrigation in the cultivation fields for fruits and vegetables, which are grown in the city of Brazlândia, was contaminated at the moment of this study. Data from the literature corroborate these findings, as they show that total coliforms and Escherichia coli (Souza et al, 1983;Silva et al, 2006;Marques et al, 2020) are often found in water and food and, when ingested by the population, can cause diseases and, in severe cases, can generate morbidity and even lead to death (Santos et al, 2017;Correa et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…The detection of fecal coliforms confirms that the water used by the population and for irrigation in the cultivation fields for fruits and vegetables, which are grown in the city of Brazlândia, was contaminated at the moment of this study. Data from the literature corroborate these findings, as they show that total coliforms and Escherichia coli (Souza et al, 1983;Silva et al, 2006;Marques et al, 2020) are often found in water and food and, when ingested by the population, can cause diseases and, in severe cases, can generate morbidity and even lead to death (Santos et al, 2017;Correa et al, 2020).…”
Section: Discussionmentioning
confidence: 84%
“…Ao confrontar os resultados de pH com os limites definidos na Resolução CONAMA nº 357/2005357/ (BRASIL, 2005, constata-se que eles estão muito próximos do limite estabelecido pela referida resolução, entre 6 e 9, para águas doces de todas as classes. A água escoada em corpos hídricos com pH ácido se ingeridos constantemente, podem ser prejudiciais à saúde humana (MARQUES et al, 2020), adicionalmente a elevação do pH aumenta a concentração da forma não iônica da amônia, ou seja, a fração tóxica da amônia na água (LIMA, 2019). Em pH mais alcalino, acima de 7, ocorre maior transformação do íon amônio (NH 4+ ) em amônia livre e gasosa (NH 3 ), tóxica aos peixes (LIMA, 2019).…”
Section: Resultsunclassified
“…At the 10 collection points, the average populations of E. coli ranged from 444 to 2,585 MPN.mL -1 . Other studies have already been carried out in Brazil on the microbiological quality of surface water and indicated high levels of contamination by microorganisms of the coliform group, resulting in inadequate sanitary conditions (Costa et al, 2020;Gonçalves et al, 2020;Marques, Nunes-Gutjahr, & Braga, 2020) and risk for multiple uses. Lack of adequate monitoring and control systems is one of the main factors that compromise water quality.…”
Section: Resultsmentioning
confidence: 99%